Research progress in interface optimization and preparation technology of high thermal conductivity diamond/copper composite materials - Xue, Yaohui; Li, Rui; Deng, Yongru; Zhang, Zhuo; Chen, Jing; Ma, Aijie; Wen, Ruilong (Frontiers in Materials, 2025)
With the miniaturization and integration of microelectronic components, the demand for high-thermal-conductivity electronic packaging materials has grown substantially. Diamond/copper (Dia/Cu) composites have become a focus of research due to their ultra-high thermal conductivity and low coefficient of thermal expansion. However, poor interfacial bonding and high interfacial thermal resistance between diamond and copper limit their practical performance. This paper reviews strategies to enhance interfacial bonding, including diamond surface metallization (e.g., electroless plating, magnetron sputtering, molten salt method, vacuum electroplating, and embedding) and copper matrix alloying (e.g., gas atomization and alloy smelting), and evaluates their effects on thermal transport properties. Additionally, the influence of preparation processes—such as vacuum hot-pressing sintering, high-temperature high-pressure sintering, spark plasma sintering, and melt infiltration on the microstructure and thermal conductivity of composites are discussed. Key factors including diamond surface roughness, particle size, volume fraction, and sintering conditions (e.g., temperature, pressure, and dwell time) are analyzed. Experimental and computational studies demonstrate that systematic optimization of these factors enhances the thermal conductivity of Dia/Cu composites, providing critical insights for developing next-generation high-performance electronic packaging materials.